Evaluation of the compression properties of co-processed paracetamol, gelatin and microcrystalline cellulose formulation prepared via melt-in agglomeration - Didacus Nnamani; Sylvester Eraga (Shiraz University of Medical Sciences, 2022)
Co-processing techniques have been used to modify the properties of dosage forms. The aim of this study is to evaluate the granules and tablet properties of co-processed paracetamol, gelatin and microcrystalline cellulose. Batches of co-processed paracetamol granules (A-E) were prepared by melt-in agglomeration process using paracetamol with varying amounts of gelatin (1.0, 2.0, 3.0 or 4.0 % w/w) or starch (3.0 % w/w) and microcrystalline cellulose. A control batch (F) of conventional granules was also prepared by wet granulation method with starch mucilage (4.0 % w/w). The granules were subjected to micromeritic, compaction and differential scanning calorimetric analyses. The granules were compressed into tablets and their tablet properties evaluated. Granules of batches A-D had higher percent maximum volume reduction of 12.25-16.13 % compared to the percent maximum volume-reduction (9.52 and 11.81) of granules from batches E and F respectively. Differential scanning result indicates amorphous solidification of co-processed paracetamol. Tablets formulated from batches A-D showed improve tensile strength (3.63 - 8.26 Nm-2) and faster disintegration time (1.32- 1.12 min) compared to the tensile strengths (5.09 & 5.01 Nm-2) and disintegration times (2.54 & 4.43 min) of tablets from batches E and F respectively. There were no significant difference (P≥0.05) in their maximum amounts ( >70 %) of drug released after 40 min. Melt-in agglomeration of paracetamol and gelatin with microcrystalline cellulose created amorphous dispersion that improved tabletability parameters of granules and disintegration time and dissolution properties of tablets.